Flexible Zinc–Air Battery with High Energy Efficiency and Freezing Tolerance Enabled by DMSO‐Based Organohydrogel Electrolyte. Issue 1 (21st November 2021) - Jiang, Dingqing; Wang, Hongyang; Wu, Shuang; Sun, Xiaoyi; Li, Juan
Abstract: With the emergence of various flexible electronics, the flexible zinc–air battery (ZAB) is considered a promising energy source with low cost, high energy density, and safety. However, gel electrolytes that improve the freezing tolerance and energy efficiency of ZABs are rarely explored. Herein, an organohydrogel electrolyte (OHE) is fabricated by soaking poly(2‐acrylamido‐2‐methylpropanesulfonic acid)/polyacrylamide (PAMPS/PAAm) double‐network hydrogel in aqueous KOH electrolyte with dimethyl sulfoxide (DMSO) additive. The prepared OHE exhibits high mechanical strength and excellent ionic conductivity. In addition, the introduction of DMSO effectively improves freezing tolerance and electrochemical performance especially in energy efficiency of ZABs due to that DMSO can break the hydrogen bonds between water molecules and alter the path of the conventional oxygen evolution reaction in ZAB simultaneously. Compared with the control hydrogel electrolyte, the optimized OHE enables flexible ZABs to not only exhibit an exceptionally low charge voltage of 1.63 V, high energy efficiency of 74.2%, and long cycling life of 177 cycles, but also to operate with an excellent specific capacity of 562 mAh g −1 and energy density of 523.4 Wh kg −1 at − 40 ° C. Moreover, the obtained flexible ZABs keep a stable output under deformations and extreme low temperature, manifesting a great potential for functional wearable devices. Abstract : A flexible zinc–air battery enabled by dimethyl sulfoxide based organohydrogel electrolyte exhibits a remarkable charge/discharge energy efficiency of 74.2% and excellent antifreezing properties even at −40 °C.